(untitled) (Colombia Medica, 2011)
Objective: To measure the effectiveness of an educational program, that encourages the adoption of healthy behaviors in caregivers, to prevent diarrheal diseases in children under five years of age.Design: Quasi experimental educational intervention (before-after type), adopting the interrupted time series design with a group (Burns and Grove 2008) and the Health Beliefs theory of Hochbaum.Materials and methods: We repeatedly measured the effect of an educational program to promote the adoption of healthy behaviors toward the prevention of acute diarrheal disease in 17 caregivers of children under 5 years of age in a marginal suburb of the city of Sincelejo (Colombia). A standardized questionnaire and a semi-structured interview was applied on two occasions (before and after) to investigate the beliefs about the perception of severity and identification of risk factors and prevention of disease, an observation guide to follow changes in beliefs was also used.Results: We found a low presence of healthy beliefs in all dimensions before the implementation of the program and a high proportion of variation of change after the intervention, except in the perception of benefits, which turned out to be the same before and after the intervention. The greatest predictor of change was the perception of the severity of the disease, with a coefficient of variation of 100%.Conclusions: The effectiveness of an educational program to adhere to an expected behavior is achieved by using the synergy of educational and communication elements in health behavior theories that go beyond the cognitive to the affective and structure of volition.